Role of sustainable aviation biofuels in the decarbonisation of aviation sector - Zheliezna, Т. (Energy and Automation, 2025)
Renewable energy, in particular bioenergy, makes a significant contribution to replacing fossil fuels and reducing greenhouse gas emissions. This is in line with the current challenge at the global level – the decarbonization of all sectors of the economy, including energy and transport. Due to the widespread use of renewable energy sources, significant progress has already been made in the decarbonization of the heat and electricity production sectors. At the same time, transport lags significantly behind these two sectors in introducing renewable energy carriers. Among other things, this is on account of the objective difficulty of electrifying the transport sector, and this especially applies to aviation and water transport. This determines an increased role of biofuels in the decarbonization of transport.Today, the contribution of aviation to the global greenhouse gas emissions does not exceed 3%. However, given the rapid development of this sector and the growth in fuel consumption in it, this contribution can increase significantly. In view of this, the International Air Transport Association and the International Civil Aviation Organization have set a goal of achieving carbon neutrality in aviation by 2050. It is important that in the implementation of this ambitious goal, 65% is allocated to the consumption of sustainable aviation fuels. In a general sense, sustainable aviation fuels are biofuels and synthetic fuels that can provide a high level of reduction in carbon dioxide emissions compared to the use of fossil fuels. The European Union also pays considerable attention to the issue of decarbonization of aviation, as evidenced by the adoption of a special ReFuelEU Aviation Regulation in 2023. This Regulation sets mandatory targets for the share of sustainable aviation fuels at all the EU airports and provides a more detailed definition of sustainable aviation fuels.The aim of the work is to identify the most promising types of sustainable aviation biofuels and kinds of feedstock for their production for the conditions of Ukraine.To achieve the goal of the work, an analysis of several fundamental aspects related to the production of sustainable aviation biofuels was performed, followed by a synthesis of the results for Ukraine’s conditions. These aspects include the current level of development and commercialization of technologies for obtaining sustainable aviation biofuels; relevant types of feedstock (biomass) and the possibilities of increasing their use; the requirements of Directive (EU) 2018/2001 (RED III) regarding the sustainability of liquid biofuels.Key words: renewable energy sources, decarbonization, sustainable aviation fuels, aviation biofuels, biomass